Transcription of the bovine parvovirus genome in isolated nuclei. - Patton, J T (1979)
Transcription of the genome of the nondefective parvovirus BPV was examined in nuclei isolated from synchronized bovine fetal spleen cells. The relative levels of total RNA polymerase and RNA polymerase I, II, and III activities in nuclei isolated from BPV-infected and mock-infected cells were found to be similar throughout the course of infection. Hybridization of RNA synthesized in isolated nuceli indicated that BPV-specific RNA synthesis began during the period of 8 to 12 h postinfection and proceeded linearly until at least 20 h postinfection. By 20 h postinfection, 5% of the total RNA synthesized in nuclei from infected cells was virus specific. BPV-specific RNA synthesis was inhibited by 95% in the presence of 0.1 microgram of alpha-amanitin per ml, suggesting that the viral genome is transcribed by cellular RNA polymerase II.